IDENTIFIKASI PANGAN LOKAL DO HUNIAN DAN SOSIALISASI PENANGANAN PANGAN TERHADAP HAMA KUTU Sitophilus Zea mays L. DENGAN PESTISIDA ALAMI - Takaeb, Matheos J; Dian R. Sabat; Halani F. Sunbanu; Christian A. N. Lasi; John Hendra Naat; Ared J. Billik (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
Research and devocation carried out the identification of the community aims to local food and socialization prevention as well as treatment of pest infestasion Sitophilus zea mays L. with natural pesticide, this activity carried out Bikekneno in the village, in South Mollo, Regency South-Central Timor, East Nusa Tenggara province. The event was held in a survey, socialization anda research into prevention as well as to pest infestation handling Sitophilus zea mays L. with natural pesticide. Based on the research food in the form of a corn plant food followed (59,6%) nut rice, arbila (19,0%), rice (13%), peanut (13%), green bean (12%), long beans (3%), squash wax (1%), and mos low (0%)beans maize. From this data be said that the village Bikekneno people food still in the form of a corn plant as prime food. Backup storage of food to villagers Bikekneno mostly kept in the furnance of fire found houselocal furnance. The food was influential storage pest shed on the growth oftenresulting in damage to food after people to harvest in the garden. If corn therefore a socialization of prevention as well as treatment of pest infestation Sitophilus zea mays L. With pesticide know the leaves of the pandanus, colored leaves, breadfruit leaves and the regulation of temperature in the good Bikekneno storage reserve in the village